2017
DOI: 10.1194/jlr.m074542
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid binding protein 4/aP2-dependent BLT1R expression and signaling

Abstract: Previous studies have shown that reduced levels of the adipocyte fatty acid binding protein (FABP)4 (AFABP/aP2), result in metabolic improvement including potentiated insulin sensitivity and attenuated atherosclerosis. Mechanistically, pharmacologic or genetic inhibition of FABP4 in macrophages upregulates UCP2, attenuates reactive oxygen species (ROS) production, polarizes cells toward the anti-inflammatory M2 state, and reduces leukotriene (LT) secretion. At the protein level, FABP4 stabilizes LTA toward che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…In proinflammatory M1 macrophages that accumulate in adipose tissue during obesity-linked metabolic diseases, UCP2 expression is blocked by adipocyte FA binding protein (FABP4/aP2), and the resulting release of redox signaling is involved in inflammasome activation and IL-1β secretion ( 161 , 385 ). Inflammasomes are cytoplasmic, multiprotein complexes involved in the sensing of danger signals, the role of which is to trigger caspase-1 activation and insufficient interleukin IL-1β maturation in response to diverse stimuli , sensed by pattern recognition receptors such as RIG-I-like receptors (sensing viral RNA), mitochondrial antiviral signaling protein, and TLR9 (sensing mtDNA).…”
Section: Involvement Of Ucps In Redox Homeostasis and Redox Regmentioning
confidence: 99%
“…In proinflammatory M1 macrophages that accumulate in adipose tissue during obesity-linked metabolic diseases, UCP2 expression is blocked by adipocyte FA binding protein (FABP4/aP2), and the resulting release of redox signaling is involved in inflammasome activation and IL-1β secretion ( 161 , 385 ). Inflammasomes are cytoplasmic, multiprotein complexes involved in the sensing of danger signals, the role of which is to trigger caspase-1 activation and insufficient interleukin IL-1β maturation in response to diverse stimuli , sensed by pattern recognition receptors such as RIG-I-like receptors (sensing viral RNA), mitochondrial antiviral signaling protein, and TLR9 (sensing mtDNA).…”
Section: Involvement Of Ucps In Redox Homeostasis and Redox Regmentioning
confidence: 99%
“…Eosinophils, through the release of various mediators, including leukotrienes, are crucial for mucus secretion in the airways and in the development of AHR (39,41). FABP4 has been shown to stabilize LTA 4 toward chemical hydrolysis, thus favoring LTC 4 synthesis (29,72), and studies have shown that LTC 4 induces chemotaxis of eosinophils and expression of the adhesion molecule Mac-1 (␣M␤2-integrin) (16). Thus absence of FABP4 is likely to contribute to the reduced levels of LTC 4 in the lungs of allergen-challenged FABP4-deficient mice, which in turn can lead to reduced eosinophil recruitment to the airways.…”
Section: L237mentioning
confidence: 99%
“…It is predominantly a cytosolic protein, which is abundantly expressed in adipocytes and macrophages (15) and is secreted by adipocytes in response to cAMP (49). In adipocytes, FABP4 serves as a lipid chaperone and facilitates hormone-stimulated lipolysis (10), whereas, in macrophages, the protein stabilizes leukotriene A 4 to hydrolysis, thereby potentiating synthesis of cysteinyl leukotriene C4 (LTC 4 ) (29,72). Studies have also demonstrated FABP4 expression in other cell types, such as dendritic cells, epithelial cells, and endothelial cells under physiological and/or pathological conditions (18).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that FABP4 can enhance insulin sensitivity and reduce atherosclerosis. Knockdown of FABP4 gene can reduce the expression of inflammation-driven macrophage receptor (16). Ning et al (17), reported that FABP4 was overexpressed in GDM patients and has a significant positive correlation with IR and inflammatory factor TNF-α, suggesting that FABP4 can be used as a new biomarker for GDM.…”
Section: Introductionmentioning
confidence: 99%